SOLAR AND SOLAR WIND ISOTOPIC COMPOSITIONS - Wiens R.C.; Bochesler P.; Burnett D.S.; Wimmer-Scweingruber R.F. (My University, 2004)
With only a few exceptions the solar photosphere is thought to have retained the mean isotopic composition of the original solar nebula, so that, with some corrections, the photosphere provides a baseline for comparison of all other planetary materials. There are two sources of information on the photospheric isotopic composition: optical observations, which have succeeded in determining a few isotopic ratios with large uncertainties, and the solar wind, measured either in-situ by spacecraft instruments or as implanted ions into lunar or asteroidal soils or collection substrates. Gravitational settling from the outer convective zone (OCZ) into the radiative core is viewed as the only solar modification of solar-nebula isotopic compositions to affect all elements.